Trends in healthcare expenditure in United States adults with chronic kidney disease: 2002-2011 - Mukoso N. Ozieh; Kinfe G. Bishu; Clara E. Dismuke; Leonard E. Egede (BMC, 2017)
Abstract Background This study examines trends in healthcare expenditure in adults with chronic kidney disease (CKD) and other kidney diseases (OKD) in the U.S. from 2002 to 2011. Methods One hundred and eighty-seven thousand, three hundred and fourty-one adults aged ≥18 from the Medical Expenditure Panel Survey (MEPS) Household Component were analyzed. CKD and OKD were based on ICD-9 or CCC codes. A novel two-part model was used to estimate the likelihood of any healthcare use and total expenditures. Covariates included individual demographics and comorbidities. Results Approximately 711 adults surveyed from 2002 to 2011 had CKD and 3693 had OKD. CKD was more likely among Non-Hispanic Blacks (NHB), Midwest and Western residents while OKD was more likely among Non-Hispanic Whites (NHW), Hispanics, married and Northeast residents. Both CKD and OKD were more likely in ≥45 years, males, widowed/divorced/single, ≤high school educated, publicly insured, Southern residents, poor and low income individuals. All comorbidities were more likely among people with CKD and OKD. Unadjusted analysis for mean expenditures for CKD and OKD vs. no kidney disease was $39,873 and $13,247 vs. $5411 for the pooled sample. After adjusting for covariates as well as time, individuals with CKD had $17,472 and OKD $5014 higher expenditures, while adjusted mean expenditures increased by $293 to $658 compared to the reference year group. Unadjusted yearly expenditures for CKD and OKD in the US population were approximately $24.6 and $48.1 billion, while adjusted expenditures were approximately $10.7 and $18.2 billion respectively. Conclusion CKD and OKD are significant cost-drivers and impose a profound economic burden to the US population.